Pemanfaatan Padi gogo sebagai Tanaman Sela Antar Tanaman Cabe di Sumatera Utara (Studi Kasus di Kab. Karo Sumatera Utara) - Marpaung, Imelda. S; Ratmini, NP Sri (Seminar Nasional Lahan Suboptimal, 2018)
Marpaung et al, 2019. Utilization of Upland Rice as Intercropping Chilli Plant in North Sumatra Province (case study in North Sumatra Karo District). pp. 442-448.Rice is one of the main comodity that the government always seeks to increase. This research was to  study utilization of upland rice as intercropping chilli in North Sumatra Province.  The decrease in rice field area for rice plants needs to be an effort to increase  rice production, one of them is by using intercropping between chilli plants. Rice cultivation as a chilli crop carried out by upland farmers in North Sumatra can provide farmers income of  Rp. 3.809.000/ 2000m2 with R/C ratio 1.74 compared to just monoculture. The intercropping of rice and chilli plants carried out for farmers is a means of fertilizer production that is more efficient and easier to use. OPT for chili plants.